Early Risk Factors for Severe COVID-19 in Adults With Hypertension - Peng, Denggao; Gao, Yanzhang; Zhou, Zhenyu; Wang, Huan; Tang, Anjue (Cardiology and Cardiovascular Medicine, 2021)
Objective Aimed to identify the early risk factors for severe COVID-19 in adults with hypertension, and provide a basis for risk stratification and treatment decisions. Methods A retrospective study was performed. Adults were defined as being more than 18 years old. Multivariate binary logistic regression analysis and Receiver Operating Characteristic (ROC) curve were used to evaluate the risk factors. Results A total of 68 COVID-19 cases with hypertension were included, 27 (39.7%) were severe and 41 (60.3%) were non-severe. Between the non-severe group (n=41) and severe group (n=27), number of elevated B-Type Natriuretic Peptide (BNP) and abnormal renal function, and albumin, lactate dehydrogenase, ultrasensitive troponin I, plasma PH value, arterial carbon dioxide partial pressure, sodium, plasma osmolality, blood glucose and ratio of arterial oxygen partial pressure (PaO2) and fraction of inspired oxygen (FiO2) were significantly different. BNP (Odds ratio [95%CI] 12.307[1.349-112.251];P=0.026), plasma osmolality (0.345[0.169-0.705];P=0.004), blood glucose (2.262[1.158-4.422];P=0.017) and PaO2/FiO2 ratio (0.267[0.124-0.577]; P=0.001) were significant independent risk factors. The area under ROC curve (AUC) of model was 0.904 ([95%CI] [0.832-0.976];P<0.001), with excellent performance. The sensitivity, specificity, positive and negative predictive value, and accuracy of predicting were 78.6%, 87.5%, 81.5%, 85.4% and 83.8%, respectively. BNP, plasma osmolality, blood glucose or PaO2/FiO2 ratio as single predictors, their AUCs were 0.624, 0.726, 0.687 and 0.75, respectively. Conclusion Decreased plasma osmolality and PaO2/FiO2 ratio, elevated BNP and blood glucose may be the early risk factors for severe COVID-19 with hypertension. Targeting osmolality regulation, early use of diuretics may be a promising treatment.